Social-emotional problems in 3-to 5-year-old children: a cross-sectional study of highly educated migrants in a Chinese urban area - Qingning Xu; Qingning Xu; Shaoying Liu; Zhijun Zhu; Jingwen Xu; Yujuan Shen; Hongyan Liu; Yanqing Zhou; Luxin Xu (Frontiers Media S.A., 2024)
BackgroundPrevious research has primarily examined the mental well-being of children from labor migrant families, yet there is a lack of understanding regarding the mental well-being of children from highly educated migrant backgrounds. This study investigated the social-emotional problems of 3-5-year-olds from highly educated migrant families residing in an urban area of China, as well as explored potential differences in demographic variables.MethodsA cross-sectional study was conducted in Qiantang District, Hangzhou, China, with 1,494 (53.3% boys) children selected via a convenient sampling method. The Ages & Stages Questionnaires: social-Emotional, Second Edition (ASQ:SE-2) was used to measure social-emotional problems.ResultsThe results showed that 23.6% of the children were at risk for social-emotional problems. More boys (26.7%) than girls (20.1%) had scores above the cut-off. Additionally, more children in the low socioeconomic status (29.9%) had scores above the cut-off than those in the high socioeconomic status (18.9%). There were three common issues among all age groups: "being more active than others," "excessive attachment to parents," and "being overly friendly with strangers.ConclusionThe social-emotional development of children from highly educated migrant families is a significant aspect that deserves recognition, contributing valuable insights to the existing literature on this topic.